Usage of whole wheat flour and bran for making macaroni products - Yurchak, Vera; Karpyk, Galina (My University, 2013)
There was also investigated the content of food fibers in the whole wheat flour and in wheat siftings, and also their quantity in the macaroni pastry under the investigation was calculated. They checked the influence of the whole wheat flour and the siftings onto the products quality. It was discovered that the usage of the whole wheat flour and the siftings promotes the increase of food fibers content in macaroni products and provides for their accepted quality according to organoleptic and physical-chemical indicators.
Keywords: macaroni products; whole wheat flour; dietary fiber; wheat bran; макаронні вироби; цільнозернове борошно; харчові волокна; пшеничні висівки; макаронные изделия; цельносмолотая мука; пищевые волокна; пшеничные отруби; кафедра технології хлібопекарських і кондитерських виробів